Kierunki i stopień wykorzystania funduszy unijnych jako źródła finansowania polityki rozwoju regionalnego - na przykładzie Dolnego Śląska - Dybał, Małgorzata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The aim of this article is to present distribution and implementation of available European Union Funds as well as structure of The Integrated Regional Operational Programme. On a basis of data from The Lower Silesia Province a trial of investments assignment to the matrix of priorities contained in the Development Strategy of Lower Silesia Province has been taken. Thereby, the trends and amount of regional development has been revealed. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 343-360